2002
DOI: 10.1145/635506.605408
|View full text |Cite
|
Sign up to set email alerts
|

Energy-efficient computing for wildlife tracking

Abstract: Over the past decade, mobile computing and wireless communication have become increasingly important drivers of many new computing applications. The field of wireless sensor networks particularly focuses on applications involving autonomous use of compute, sensing, and wireless communication devices for both scientific and commercial purposes. This paper examines the research decisions and design tradeoffs that arise when applying wireless peer-to-peer networking techniques in a mobile sensor network designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(23 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…• Mobile embedded sensor: In this type of sensor, their movement is controlled by external force, like wildlife tracking [96] or tracking cooperative nodes [97]. Another typical example for embedded sensors can be found in [98][99][100].…”
Section: Mwsns Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…• Mobile embedded sensor: In this type of sensor, their movement is controlled by external force, like wildlife tracking [96] or tracking cooperative nodes [97]. Another typical example for embedded sensors can be found in [98][99][100].…”
Section: Mwsns Architecturesmentioning
confidence: 99%
“…• Data mule: Predominantly, in this kind which is called a data mule [96], the sensor nodes do not work as mobile; they just collect the data and sent the collected data to the base station.…”
Section: Mwsns Architecturesmentioning
confidence: 99%
“…Currently, several OMN based wildlife monitoring projects are proposed for sensor data gathering, e.g. ZebraNet [3,9], Rat Watch [10]. These works, implement opportunistic networks by leveraging a history based flooding, which are prone to low delivery ratio and high latency [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the gathered data is transfered to a sink using intermediate nodes as fixed relays. However, traditional routing protocols will perform poorly in WMS scenarios where the network is sporadically connected due to animal mobility pattern [9]. Currently, several research works have shown an improved data collection based on opportunistic sensing with fixed network infrastructure support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation